Toward Women-Friendly Mosques (American Journal of Islam and Society, 2005)
The Islamic Social Services Association and Women in Islam have releaseda guide underlining a set of principles rooted in Islamic sources that outlinesthe rights of Muslim women to have full access to the mosque, and callingon Muslim leaders to privilege Islamic principles and values over culturalhabits and traditions. The guide is entitled “Women-Friendly Mosques andCommunity Centers: Working Together to Reclaim Our Heritage.”The guide is a serious attempt to deal with an issue that requires immediateattention by Muslim communities: the place of women in the mosqueand the community. I personally faced the issue for the first time twodecades ago when a Muslim Student Association board member objectedto the inclusion of women in an executive meeting. He based his positionon Islamic tradition, but his argument was found lacking by everyone elseon the board. The meeting went on without him, but with the two sisters.The point of view alluded to above has continued to be well-representedover the years within the Muslim community, particularly among immigrantswho grew up in societies were women did not take an active role insocial life and community development. The point of view that was hostileto the presence of women in the mosque gained more of a following inmany Islamic centers throughout North America as the community grewmore dependent on imams and scholars educated in universities that providea narrow Islamic education.Hammered by Islamic opinions apparently rooted in Islamic sources,many mosques started to erect barriers and drop curtains between the men’sand women’s areas. Eventually, many mosques designated a separate andsecluded area for Muslim women. The strict seclusion often mimickedarrangements adopted by mosques in Muslim countries and was toleratedby women who grew up in a condition of seclusion.American-born Muslim women, including women who grew up inimmigrant families, find it increasingly difficult to accept the regime ofseclusion in the mosque that cuts them off from education and decisionmaking. Some have chosen to stay away and find alternative ways toacquire Islamic education and engage in social services. Others went backto understand Islamic sources and found out that there is no ground for theregime of seclusion.The “Women-Friendly Mosques” guide is the outcome of a quest byMuslim women who made the journey to examine the Islamic sources andto face head-on the arguments employed to perpetuate a regime that cutsMuslim women off from Islamic education and community service. Thejourney placed them in direct contact with the Islamic texts and put them intouch with Muslim scholars. The conclusion they came back with is bothrefreshing and relieving for every Muslim woman who was troubled withthe sense of alienation that she had developed by visiting the center ofIslamic life, whose Prophet, peace be with him, came to reaffirm the spiritualand moral equality of both men and women.